PSYCHOSEMANTICS WHICH FAMILIES ADOLESCENTS WITH DIFFERENT ADAPTIVE PERSONAL STATUS - Anastasiya Vasilievna Berlovskaya (Вестник Северо-Кавказского федерального университета, 2022)
Аnalyzes the image of the family in modern psychology within psychosemantic approach, a study to identify the semantic space of the image of the family in adolescents with different adaptation status to update their adaptive capacity to create their own families and the successful integration of social reality. For the analysis of the image of the family used the method of semantic differential Charles Osgood.